1-Ethyl-3-methylimidazolium tartrate chiral ionic liquids: preparation, characterization and opportunities thereof. (30th October 2018) - Castellan, Tessa; Cuyamendous, Claire; Fitremann, Juliette; Galano, Jean-Marie; Oger, Camille; Durand, Thierry; Guillen, Frédéric; Génisson, Yves
Abstract : Eight tartrate-based imidazolium salts were obtained as synthetically useful chiral ionic liquids with chirality-dependent physico-chemical properties. Abstract : A unified acid/base synthetic access to tartrate-based chiral ionic liquids relying on the generation of cation hydroxide salts with AgOH was challenged with the preparation of sensitive 1-ethyl-3-methylimidazolium derivatives. Systematic variation of the starting tartaric acid stoichiometry and configuration led to eight stereoisomeric 1-ethyl-3-methylimidazolium hydrogen tartrate or di-(1-ethyl-3-methylimidazolium)tartrate entities. These salts were all characterised as proper ionic liquids. An unprecedented influence of the configuration ((2 S, 3 S ), or (2 R, 3 R ) vs. racemic or meso ) on dynamic viscosity was observed. The relevance of such tartrate salts as task-specific ionic liquids was demonstrated in a synthetically useful base-promoted intramolecular cyclisation of a C 2 -symmetrical bis-epoxide en route to the total synthesis of phytofuran metabolites.